The Application of Information-Motivation-Behavioral Skills Model in Caring for Elderly Person among Coronavirus 2019 (COVID-19) Pandemic - Iamming, Pattamapron; Kruangkaew, Phatcharawan (NU Journal of Nursing and Health Sciences, 2023)
This academic article aims to study the guidelines for caring for the elderly and caregiver during the Coronavirus (covid-19) epidemic. Applying Information-Motivation-Behavioral Skills model of Fisher et al. This concept consists of 3 components: 1) Information Including basic knowledge about the Corona virus 2019 and Knowledge of self-care from Corona virus infection 2019. 2) Motivation for prevention of infection of oneself and those around them, including attitudes to prevent infection with the Corona virus 2019. And 3) Behavioral skills for infection prevention, including wearing a mask, 7 steps of handwashing with soap and alcohol, Social distancing. The concept is believed that if a person has these 3 elements, it will result in appropriate and sustainable behavioral change in self-care in the Coronavirus 2019 epidemic. Therefore, the Public health agencies are an important part that can apply this approach in the care and prevention of infection in the elderly who live at home, including nursing homes during the outbreak of the Coronavirus 2019.